Given the equation,
![-9x^2+72x+16y^2+16y+4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/bvq1ykoevq1glmh86deknkk3qspo2z7jr9.png)
Complete squares as shown below,
![\begin{gathered} -9x^2+72x-a^2=-(9x^2-72x+a^2)=-9(x^2-8x+b^2) \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/hyx1addauv38w7iousfj7evfwf0df3eswl.png)
Thus,
![\begin{gathered} \Rightarrow-9x^2+72x-a^2=-9(x^{}-4)^2 \\ \Rightarrow a^2=16\cdot9=144\Rightarrow a=12 \\ \Rightarrow-9x^2+72x-144=-9(x^{}-4)^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/7ozqsl3y15oko4upcb0csodg26qjltw7n5.png)
Similarly,
![\begin{gathered} 16y^2+16y=16(y^2+y) \\ \Rightarrow16(y+(1)/(2))^2=16(y^2+y+(1)/(4)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/bk0ow49o03yfargwl39yy78tjj15nv68rp.png)
Therefore,
![\begin{gathered} -9x^2+72x+16y^2+16y+4=0 \\ \Rightarrow-9(x-4)^2+16(y+(1)/(2))^2+4=-144+4 \\ \Rightarrow-9(x-4)^2+16(y+(1)/(2))^2=-144 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/rs0633mly55f1mxjvr5h5rowq9jwqarp49.png)
Finally, the standard form is.
![\begin{gathered} \Rightarrow-((x-4)^2)/(16)+((y+(1)/(2))^2)/(9)=-1 \\ \Rightarrow((x-4)^2)/(16)-((y+(1)/(2))^2)/(9)=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/pkig4cm9m700vg7r5rubkq3a6ie3pxujm0.png)
As for the vertices, foci, and asymptotes,
![\begin{gathered} c=\pm\sqrt[]{16+9}=\pm5 \\ \text{center:}(4,-(1)/(2)) \\ \Rightarrow\text{foci:}(4-5,-(1)/(2))_{},(4+5,-(1)/(2))_{} \\ \Rightarrow\text{foci:}(-1,-(1)/(2)),(9,-(1)/(2)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/1rhu9g7hkz3afsu1vnydq39ycmyihayorw.png)
Foci: (-1,-1/2), (9,-1/2)
Vertices
![\begin{gathered} \text{center:}(4,-(1)/(2)),\text{vertices:}(4\pm a,-(1)/(2)) \\ \text{vertices:}(4+4,-(1)/(2)),(4-4,-(1)/(2)) \\ \text{vertices:}(8,-(1)/(2)),(0,-(1)/(2)) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/3tc7gwca4bprvndt4fozsirgtabagtdmm0.png)
Vertices: (8,-1/2), (0,-1/2)
Asymptotes:
![\begin{gathered} y=\pm(3)/(4)(x-4)-(1)/(2) \\ \Rightarrow y=(3)/(4)x-(7)/(2) \\ \text{and} \\ y=-(3)/(4)x+(5)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/vc9x66hjzsln3squb4zfzfixegj44l0g6l.png)
Asymptotes: y=3x/4-7/2 and y=-3x/4+5/2